Theoretical Modeling and Optimization of the Detection Performance: a New Concept for Electrochemical Detection of Proteins in Microfluidic Channels - Amatore, C.; Oleinick, A.; Svir, I.; da Mota, N.; Thouin, L. (Nonlinear Analysis: Modelling and Control, 2006)
In this work, we present a complete theoretical analysis of a new concept of electrochemical detector for application in proteomics upon considering two band microelectrodes performing in generator-collector mode. This concept of an original electrochemical detector is aimed at the detection of proteins following their separation in microfluidic biochips. The theoretical analysis is based on the use of the time-dependent coordinate transformation which allows performing precise modeling for a wide range of the key parameters governing the electrochemical detector performance. This allows defining a precise optimization procedure for its best efficiency upon considering the qualitative and quantitative effects of each of the main operational parameters.